EKSISTENSI TRADISI TEPUNG TAWAR SEBAGAI WARISAN BUDAYA LOKAL PALEMBANG - Syarifuddin, Syarifuddin; Rezeki, Wanada; Kalsum, Umy (Sejarah dan Budaya: Jurnal Sejarah, Budaya, dan Pengajarannya, 2022)
This study aims to introduce the history and local culture of Palembang to the community and as a form of elevating the existence of the fresh flour tradition as Palembang's local cultural heritage. This study focuses on the fresh flour tradition that developed in the people of Palembang City by discussing several aspects of this tradition, namely history, purpose, implementation/procession, existence, meaning and symbol, as well as efforts to preserve the fresh flour tradition. In this study using historical research methods with four stages in the research process, namely heuristics, criticism, interpretation, and historiography. The results of the study found that: (1) the history of the fresh flour tradition is unknown from when it was used but basically this tradition is a form of local culture alkuturation with Hindu culture, which was then Islamized according to Islamic teachings without eliminating the existence of the tradition; (2) the fresh flour tradition is carried out mainly for the purpose of avoiding calamity and misfortune, on the other hand this tradition is also a form of request and prayer to Allah SWT; (3) the ceremonial implementation of the fresh flour tradition is to prepare chicken-roasted turmeric glutinous rice, which will later be fed to the members of the executor of the traditional activities; (4) the existence of the fresh flour tradition has existed for a long time and is known as a tool for social control and conflict resolution in the community, but nowadays people rarely do it; (5) the meaning of fresh flour is goodwill which is meant to neutralize everything for the better and symbol of the fresh flour is sticky rice with turmeric and grilled chicken. Penelitian ini bertujuan untuk memperkenalkan sejarah dan kebudayaan lokal Palembang kepada masyarakat dan sebagai bentuk mengangkat eksistensi tradisi tepung tawar sebagai warisan budaya lokal Palembang. Penelitian ini berfokus pada tradisi tepung tawar yang berkembang di masyarakat Kota Palembang dengan membahas beberapa aspek dari tradisi ini, yaitu sejarah, tujuan, pelaksanaan/prosesi, eksistensi, makna dan simbol, serta upaya pelestarian tradisi tepung tawar. Dalam penelitian ini menggunakan metode penelitian sejarah dengan empat tahapan dalam proses penelitiannya, yakni heuristik, kritik, interprestasi, dan historiografi. Hasil penelitian menemukan bahwa: (1) sejarah tradisi tepung tawar tidak diketahui mulai dari kapan digunakan namun pada dasarnya tradisi ini merupakan wujud alkuturasi budaya lokal dengan budaya Hindu, yang kemudian di islamisasikan sesuai ajaran Islam tanpa menghilangkan eksistensi dari tradisi tersebut; (2) tradisi tepung tawar dilaksanakan utamanya untuk tujuan menghindarkan diri dari malapetaka dan kemalangan, disisi lain tradisi ini juga menjadi bentuk permohonan dan doa kepada Allah SWT; (3) pelaksanaan seremonial dari tradisi tepung tawar ialah dengan menyiapkan nasi ketan kunyit panggang ayam, kemudian nantinya akan disuapkan kepada anggota pelaksana kegiatan tradisi tersebut; (4) eksistensi tradisi tepung tawar sudah ada cukup lama dan dikenal sebagai alat kontrol sosial dan penyelesaian konflik di masyarakat namun saat ini masyarakat sudah jarang melakukannya; (5) makna dari tepung tawar adalah niat baik yang dimaksudkan untuk menetralkan segala hal menjadi baik dan simbol tepung tawar adalah ketan yang diberi kunyit dan panggang ayam.